At the Crossroads of Developmental Plasticity: Epigenetic and Endocrine Regulators Mediate Environmental Influence in Fire Ant Development - Bahramifarid, Navid (Université d'Ottawa / University of Ottawa, 2026)
From plants to animals, our genomes are responsive to environmental variation, the interaction of which has profound consequences on our life-history and evolution. Environmental variation can influence developmental processes, and gene-by-environment interactions (GxE) have been shown to be mediated by the action of hormones and epigenetic mechanisms including histone modifications. Ants are an emerging model organism to study how these regulatory mechanisms facilitate development in response to environmental variation. Ant development is plastic: environmental changes can generate diverse phenotypic variation, generating individuals of different castes that vary in several traits including size, behaviour, and reproduction. We are beginning to understand how hormonal and epigenetic mechanisms can play a role in generating caste-specific trait variation. However, the interplay of these mechanisms and the process by which they mediate environmental variation to produce trait variation in ants remains enigmatic. Here, we use the highly invasive fire ant Solenopsis invicta known for both its extreme size variation in the worker caste and its adaptability to highly variable and stressful environments, to investigate the interplay of GxE mechanisms in response to environmental variation. We found that size variation and developmental timing are both thermally and nutritionally plastic. Next, we show that sizing and developmental timing are influenced by the key insect hormones juvenile hormone and ecdysone, as well as by histone modifiers, and that these regulators are both thermally and nutritionally plastic. Finally, we show the interaction of hormones and histone modifier activity. Collectively, this data suggests that size plasticity in ants is influenced by multiple environmental cues and that hormones and epigenetic processes together orchestrate this response. More generally, understanding the influence of the environment on regulatory mediators of developmental plasticity may provide insight into the mechanistic crosstalk underlying conserved developmental pathways of insect growth.
Keywords: Developmental plasticity; Temperature; Nutrition; Endocrine signalling; Developmental epigenetics; Histone modifiers; Fire ants; Developmental timing; Ecdysone